Cross-conjugated n-type polymer acceptors for efficient all-polymer solar cells. Issue 18 (8th January 2018) - Xie, Ruihao; Chen, Zhiming; Liu, Yan; Wang, Zhenfeng; Chen, Zhongxin; Ying, Lei; Huang, Fei; Cao, Yong
Abstract : Cross-conjugated polymers with different side chains were developed as the electron accepting material for all-polymer solar cells. Abstract : We designed and synthesized a series of n-type cross-conjugated polymers with a donor–π-bridge–acceptor structure (D–π-bridge–A) which can be used as electron-accepting materials to construct efficient all-polymer solar cells (all-PSCs). The two-dimensional architecture allows for the formation of cross-conjugation, which is favorable for charge carrier transport and light harvesting. Bulk-heterojunction all-PSCs based on these cross-conjugated electron-accepting polymers and PTB7-Th as the electron-donating polymer achieve an impressive power conversion efficiency of 5.55%. This cross-conjugated architecture provides a new molecular design strategy for n-type conjugated polymers.